Social Protests in 2011: International Perspective and Information Access - E. Ilikova, Lilia; Svirina, Anna (International Journal of Criminology and Sociology, 2022)
The paper analyzes the interrelation of social protesting and informal economy, core values of protesting class and the level of information accessibility for the ones involved in social unease. To perform this analysis we have used both quantitative and qualitative data: qualitative data was related to the core values of protestants and was collected via semantic analysis of their social media posts. To perform quantitative evaluation, we have used the rankings on Internet freedom and mass media transparency; yet as the main analytical tool was semantic, the conclusion on how core values influence person’s desire to be involved in social protests was made on the basis of qualitative analysis. The research had confirmed that growth rate of informal economy is a good predictor of possible unease based on dignity-based values.